Watch out for bears! : the adventures of Henry and Bruno - Wolff, Ferida, 1946-; Sneed, Brad (New York, N.Y. : Random House, 1999)
Henry and Bruno the bears become friends and they share Henry's honey, Henry's house, and a camping trip.
1.5
K-3
K-3
School Library Journal
230
Keywords: Bears -- Fiction; Friendship -- Fiction; Bears -- Fiction; Friendship -- Fiction